(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Tau protein is a microtubule-associated protein that acts as a three-dimensional “railroad tie” for the microtubule. Accumulation and Aggregation of the Tau is the pathogenesis of Alzheimer’s disease. Risk factors like ApoE risk alleles, changes in the endoplasmic reticulum, and Kinases and phosphatases dysregulation have identified as the most critical factors. In Tau pathology, the abnormal hyperphosphorylation of tau appears as its accumulation in the affected neurons in Alzheimer’s disease. Neurofibrillary Tangles has shown truncated tau in both Glu-391 and Asp-421. Truncated tau associated with apoptosis in cultured cells. All six molecules of tau are the hyperphosphorylated state in PHF. In AD, hyperphosphorylated tau is present as a cytosolic protein and PHF. Treatments related to tau pathology are under research. Tau phosphorylation inhibitors and Tau aggregation inhibitors tested in people with AD. In tau phosphorylation inhibitors, Lithium has multiple targets and inhibits GSK-3b, and in tau aggregation inhibitors, many drugs block aggregation of tau in cell-free conditions. Methylene blue has multiple targets; it slows disease progression. Tau pathology appears to be a primary cause of neurodegeneration in AD. Risk factors showed a relation between AD and Tau pathology clearly. Abnormal hyperphosphorylation of tau leads to AD, and truncated tau is the main finding in tau pathology. Tau phosphorylation inhibitors and Tau aggregation inhibitors are emerging treatments.